NOWY KURS PREZYDENTA UKRAINY - Ilnicki, Marek (Zeszyty Prawnicze, 2016)
The New Policy Adopted by Ukraine’s President Summary This article discusses the changes in Ukrainian policy since the beginning of Petro Poroshenko’s presidency. Poroshenko, the winner of Ukraine’s presidential election of 25th May 2014, launched his campaign with the slogan “A New Lifestyle” – patently inspired by Franklin D. Roosevelt’s New Deal. The way the new President and government of Ukraine have been exercising power shows that they intend to pursue a long-term policy for the enhancement of the Ukrainian economy by means of neoliberal instruments, such as, for example, the privatisation of inefficiently managed state entities, the liberalisation of prices and tariffs, a war on corruption, the implementation of decentralising measures, the removal of administrative barriers, and support for medium and small businesses. The author observes a similarity between Roosevelt’s New Deal and Poroshenko’s New Lifestyle, particularly in the latter’s endeavour to cope with a deep political and economic crisis. His efforts are being backed by the nation’s support, despite the inauspicious conditions. The author also notes that the armed conflict in Eastern Ukraine is an additional factor aggravating efficient government and the implementation of reforms. There is a potential for a change in the traditional rationale splitting Ukraine along an east—west divide, due to the fact that Poroshenko, who has the reputation of a moderate, won more votes in the traditionally nationalist Western Ukraine, than in Eastern Ukraine, where his lead in the election over radical and nationalist candidates was substantially narrower. The author is of the opinion that this development offers a prospect for a reorientation in the hitherto bipolar division in Ukrainian society. The biggest challenge facing Ukraine’s new President and government is political and financial decentralisation. The author draws a comparison between Ukraine’s current situation and the French Republic, which is a unitary, centralised, and monocentric state. To stabilise the situation in Ukraine, Poroshenko will need to normalise the country’s relations with the Russian Federation, which in view of Russia’s annexation of Crimea and the Russian military intervention in Eastern Ukraine, will call for a far greater effort than what was expected of his predecessors.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />